Review key features and advantages of USB - Здищук, С. В. (Eastern-European Journal of Enterprise Technologies, 2009)
This overview article shows us in short form main advantages of the USB over other system ports and buses as the base platform for peripheral development. Also it can be a base source for non professional developers, who want to improve their knowledge about USB.